การเกิดขึ้นของวิกฤต PM 2.5 และวิธีการรับมือของประชาชนกับการทำงานของภาครัฐ พร้อมทั้งการหาวิธีรับมือของนักปกครองรุ่นใหม่ - วิสุทฺธิญาโณ (โม้แหยม), พระวิชรญาณ; เหมือยไธสง, อภิชิต; อภิปุญฺโญฺ (พันทะลี), พระณัฐวุฒิ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 1 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 1 : มกราคม - เมษายน 2568, 2025)
Over the past decade, Thailand has been grappling with the escalating problem of fine particulate matter (PM2.5), which has increasingly impacted public health, the economy, and the environment on a broad scale. Despite government measures and public adaptation efforts, there remain significant limitations in achieving sustainable management, particularly in the areas of law enforcement and air quality data management. This article aims to propose strategies for public response, outline the role of governmental bodies, and introduce proactive governance approaches for the new generation of administrators to address the PM2.5 problem effectively and sustainably. The crisis of PM2.5 has evolved into an environmental and public health emergency that directly affects the quality of life in many regions of Thailand. Fine particulate matter can penetrate the respiratory system and bloodstream, leading to both short-term and long-term health effects. The sources of PM2.5 pollution stem from both natural phenomena and human activities, such as industrial and transportation-related combustion, agricultural burning, and forest fires across various regions. Effective responses to PM2.5 require the participation of all sectors. Citizens have adapted through personal protective measures such as wearing masks, reducing outdoor activities during high pollution periods, changing energy consumption behaviors, and advocating for more effective governmental interventions. Simultaneously, the government plays a critical role in managing the PM2.5 issue through policy formulation, pollution control legislation, enforcement of emission regulations, and the promotion of open burning reduction measures. However, state operations continue to face several challenges, including uneven enforcement, lack of inter-agency coordination, and deficiencies in air quality data management. For the new generation of administrators, confronting the PM2.5 crisis demands a proactive governance mindset, the integration of interdisciplinary knowledge, and the application of digital technologies for monitoring, alerting, and managing air quality. Initiatives such as the development of smart cities with clean transportation systems and incentive mechanisms to engage both the private sector and the public in air pollution reduction efforts are essential. This article thus examines public coping measures for PM2.5, the roles and challenges faced by the government in addressing the issue, and governance strategies that new-generation administrators can adopt to enhance the effectiveness and sustainability of problem-solving mechanisms.